2007
DOI: 10.1021/jp068562d
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Electron-Induced Oligomerization of Condensed Carbon Tetrachloride

Abstract: The low-energy electron-induced chemistry of condensed CCl 4 has been investigated with use of post-irradiation temperature-programmed desorption. These experiments were partly motivated by the growing interest in developing facile and economical methods for decomposing CCl 4 and other halocarbons which through widespread use in industry have become potent environmental pollutants. The experimental procedure involves low-energy (50 eV) electron irradiation (fluence e2 × 10 16 electrons cm -2 ) of nanoscale thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
(146 reference statements)
0
6
0
Order By: Relevance
“…To provide complementary information on electron stimulated reaction mechanisms, growth processes, and the influence of irradiation time on the film’s structure, separate experiments were performed under ultrahigh vacuum (UHV) on nanometer scale thick 1,2-DAP films. The value of this UHV experimental approach to probe electron-mediated processes has been demonstrated in recent studies relevant to atmospheric chemistry, astrochemistry, , astrobiology, thin film modification, and radiation damage to biologically relevant molecules. ,, …”
Section: Introductionmentioning
confidence: 98%
“…To provide complementary information on electron stimulated reaction mechanisms, growth processes, and the influence of irradiation time on the film’s structure, separate experiments were performed under ultrahigh vacuum (UHV) on nanometer scale thick 1,2-DAP films. The value of this UHV experimental approach to probe electron-mediated processes has been demonstrated in recent studies relevant to atmospheric chemistry, astrochemistry, , astrobiology, thin film modification, and radiation damage to biologically relevant molecules. ,, …”
Section: Introductionmentioning
confidence: 98%
“…Under these conditions, the effects of electrons on the adsorbed molecules can be monitored in situ using surface analytical techniques. Indeed, this experimental approach has been successfully employed in a number of recent studies designed to examine electron mediated processes relevant to atmospheric chemistry, astrobiology, the modification of organic films including self-assembled monolayers, and radiation damage to biologically relevant molecules. ,, In regard to electron stimulated reactions of organometallic precursors, Yates et al have studied the effect of low-energy (2−27 eV) electrons on the decomposition of hexafluoracetylacetonate Cu(I) vinyltrimethylsilane, a metal−organic chemical vapor deposition (MOCVD) precursor used for the deposition of copper, on the Si(7 × 7) surface at room temperature . X-ray photoelectron spectroscopy (XPS) results showed that electron stimulated reactions led to the formation of Cu(0) while the threshold for decomposition was ≈4 eV, consistent with a dissociative electron attachment mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable studies have been performed on the electron-induced surface reactions of several EBID precursors such as hexafluoracetylacetonate copper(I) vinyltrimethylsilane, metal carbonyls, and more recently Au III (acac)Me 2 and MeCpPtMe 3 . UHV surface science studies have also proved effective in studying other electron-mediated processes, including chemical and physical transformations initiated in organic thin films. …”
Section: Introductionmentioning
confidence: 99%